Mood disorders do not predict a more difficult course after primary anatomic total shoulder arthroplasty. Issue 3 (May 2019) - Lonergan, Timothy M.; Villarreal, Arturo D.; Smith, Richard A.; Brolin, Tyler J.; Azar, Frederick M.; Throckmorton, Thomas W.
Abstract : Background: Mood disorders are present in up to 30% of patients with arthroplasty procedures, but information is lacking about their impact on shoulder arthroplasty. As risk stratification models for bundled payment programs develop, this information becomes increasingly relevant because these plans typically are tied to 90-day episode of care. We studied the effect of mood disorders on pain, narcotic use, length of hospital stay, and complications following primary anatomic total shoulder arthroplasty (TSA) in this period. Methods: Patients with mood disorders were identified by notation of depression and/or anxiety on intake forms or use of prescription mood stabilizers. Visual analog pain scores (VAS) were recorded at the preoperative visit and at 2-, 6-, and 12-weeks after surgery. Oral morphine equivalents (OME) were recorded for in-hospital use, discharge medications, and prescriptions given at 2-, 6-, and 12-weeks. Length-of-stay and complication data also were recorded. Results: Of 133 primary anatomic TSAs, 29 patients (32 shoulders) had mood disorders, 101 did not. There were no significant differences between groups regarding age, operative indication, body mass index (BMI), or comorbidities; no significant differences in VAS scores or OME narcotic use at any of the recorded time points and no statistically significant differences in length of hospital stay or postoperative complications. Conclusions: Patients with a mood disorder can expect a postoperative course similar to patients without depression or anxiety. A mood disorder does not appear to be a significant risk factor for bundled payment plans to consider when developing predictive modeling for primary anatomic TSA. Level of Evidence: Level III, retrospective case-control prognostic study